Does Compliance Auditing Affect Bond Yields? Evidence from the Municipal Bond Market - Courson, Bethany A. (The Accounting Review, 2026)
ABSTRACT I use a unique setting in the municipal bond market to examine the impact of compliance auditing on bond yields. SEC Rule 15c2-12 requires bond issuers to provide annual financial and operating disclosures to investors over the life of the bonds. Due to concerns of noncompliance, Louisiana passed a state law requiring auditors to test for compliance with Rule 15c2-12. I find that bond yields in the municipal bond market decrease by 21 basis points after the audit law for previously noncompliant issuers in Louisiana. I find similar results when I separately examine the primary and secondary markets. I also find that previously noncompliant issuers file 75.2 percent more annual disclosures after the audit law, suggesting that the audit law improved compliance with Rule 15c2-12. Overall, my findings inform policymakers and regulators on the role of auditing over compliance with disclosure regulation as a mechanism to protect investors. JEL Classifications: G28; H74; K22; M42.